Investigating the Impact of Project Definition Clarity on Project Performance: Structural Equation Modeling Study - Xia, B.; Xiong, B.; Skitmore, M.; Wu, Peng; Hu, F. (2016)
Having a clear project definition is crucial for successful construction projects. It affects design quality, project communication between stakeholders, and final project performance in terms of cost, schedule, and quality. This paper examines the relationship between project definition and final project performance through a structural equation model comprising four latent constructs and six path hypotheses using data from a questionnaire survey of 120 general contractors in the Malaysian construction industry. The results show that in the study population all three items impact the project performance, but the link between design quality and project performance is indirect. Instead, the clarity of project definition affects project performance indirectly through design quality and project communication and design quality affects project performance indirectly through project communication. The primary contribution is to provide quantitative confirmation of the more general statements made in the literature from around the world and therefore adds to and consolidates existing knowledge. Practical implications derived from the finding are also proposed for various project stakeholders. Furthermore, as lack of the clarity of project definition is a very common occurrence in construction projects globally, these findings have important ramifications for all construction projects in expanding and clarifying existing knowledge on what is needed for the successful delivery of construction projects.